Surgical outcomes of tragal island cartilage and temporal muscle fascia grafts in tympanoplasty - Mutlu, Önder; Okuyucu, Şemsettin; Gümüş, Ramazan; Gözel, Serhat (ENT Updates, 2012)
Objective: We aimed to compare the efficacy of temporalis muscle fascia and tragal cartilage island grafts after tympanoplasty in terms of functional hearing outcomes and tympanometric findings. Methods: A total of 42 patients were enrolled in this study and Group 1 including 14 patients was defined as fascia group while Group 2 including 28 patients was defined as tragal cartilage group. After preoperative odiometric and typmpanometric measurements were done, grefts were laid as under-overlay with the same surgical technique. Only patients with intact grafts at the end 6th month of observation period were included in the study. Surgical outcomes were compared with respect to preoperative and postoperative 6th month odiometric and tympanometric findings within and between the two groups. Results: Postoperative pure tone audiometric results were significantly better than preoperative values in both groups (p=0.001 for fascia graft; p0.05) at pure tone audiometric and tympanometric results between fascia and cartialge groups regarding the pre and postoperative tests. Conclusion: Tragal cartilage island graft provides satisfactory outcomes in tympanoplasty in terms of both functional hearing results and resistance against retraction and resorption. However, it must be kept in mind that constriction of middle ear volume after use of tragal cartilage grafts in tympanoplasty is not uncommon.